Methotrexate-Related Lymphoproliferative Disorder Presenting with Severe Swelling of the Elbow Joint: A Case Report. Issue 3 (July 2017) - Hatano, Takashi; Ohishi, Masanobu; Yoshimoto, Goichi; Yamauchi, Moriyasu; Maekawa, Akira; Yamamoto, Hidetaka; Oda, Yoshinao; Endo, Makoto; Bekki, Hirofumi; Matsunobu, Tomoya; Nakashima, Yasuharu; Okazaki, Ken; et al.
Abstract : Case: A patient with rheumatoid arthritis (RA) who was being treated with methotrexate (MTX) therapy presented with severe swelling of the left elbow. Magnetic resonance imaging showed a tumor-like lesion around the elbow joint. Fluorodeoxyglucose positron emission tomography indicated multiple lesions in the lung and the lymph nodes. An open biopsy of a cervical lymph node was performed, and MTX-related lymphoproliferative disorder (MTX-LPD) was diagnosed. After cessation of the MTX therapy, the elbow swelling regressed, and the patient was in remission of MTX-LPD. Conclusion: MTX-LPD should be considered in the differential diagnosis when a patient with RA develops severe joint swelling while on MTX therapy.